2013
DOI: 10.1186/2041-1480-4-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic enhancement of drug product labels to support drug safety, efficacy, and effectiveness

Abstract: Out-of-date or incomplete drug product labeling information may increase the risk of otherwise preventable adverse drug events. In recognition of these concerns, the United States Federal Drug Administration (FDA) requires drug product labels to include specific information. Unfortunately, several studies have found that drug product labeling fails to keep current with the scientific literature. We present a novel approach to addressing this issue. The primary goal of this novel approach is to better meet the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Studies have shown product labeling to be incomplete [19], [20] and one motivation for this activity is to extend previous pilot work on methods to address known limitations of the information source [21]. To do this, we examined cases where there existed an overlap between the PDDI datasets designed for NLP research with product labeling and other data sources.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown product labeling to be incomplete [19], [20] and one motivation for this activity is to extend previous pilot work on methods to address known limitations of the information source [21]. To do this, we examined cases where there existed an overlap between the PDDI datasets designed for NLP research with product labeling and other data sources.…”
Section: Methodsmentioning
confidence: 99%
“…This has been aided by the growing availability of consolidated databases. Besides HTS assays, new data streams can include text annotations automatically mined from biomedical literature (ChemoText [52]), product labels (SIDER) [5355] and clinical notes [56,57]. …”
Section: Integrative Approach Combining Cheminformatics and Bioinformmentioning
confidence: 99%
“…The number of drugs that might need to be addressed (more than 16,000) and the complexity of the content in the SPLs make this a daunting task. Our experience in building NLP tools for the extraction of PDDI information [ 10 , 14 ] illustrated some of the difficulty and led us to the conclusion that some amount of manual involvement in the process was required.…”
Section: Discussionmentioning
confidence: 99%
“…In prior work, we developed a prototype system that used simple named entity recognition (NER) and Semantic Web Linked Data [ 9 ] to link claims about PDDIs from publicly available external resources to the Drug Interactions section of the product label [ 10 ]. Experiments found that our system linked at least one potentially novel interaction (ie, not mentioned in the label) to the Drug Interactions section of product labeling for 20 antidepressants.…”
Section: Introductionmentioning
confidence: 99%